EUTHANASIA IN IRANIAN AND EGYPT LAW - Badr Soudani Saadery (European Scientific Journal, ESJ, 2014)
The issue of Euthanasia is one of the most significant topics of legal medicine and criminal law in most countries. This issue has occupied all religious and signify circles around the world. It happens in situations in which the patient is incurable and in great pain and distress thus asking the doctor terminates his life fool of pain and misery. This act will receive controversial vacations form. Religious scientific and social circles some of the above circles have offered reasons. In this study we are going to consider the laws of the two Muslim countries Iran and Egypt on the issue of Euthanasia and the question of causing death painlessly in an incurable patient out of mercy will be considered in the laws of the two countries to see if it is homicide or not? In Islamic views, human life is so sacred that the holy Quran clearly states that if anyone saves a life, it would be as if he saved the life of the whole people. In Islam life is entrusted to people to care, nurture and safe keep. According to Islamic viewpoints a person does not own his/her body, so he is not permitted to do as he wishes to this body; Islam believes that the Almighty Allah has given us life and he only can take it away, therefore, ending a life personally or having some one to do it to relieve his pain and suffering is not only a crime, but also an unforgivable sin. The Shari'a has great details about the conditions were taking someone's life is permissible. Although Islam too puts great value on the quality of life over the length, in no respect the permission for killing a person in order to relive him of pain and suffering is granted. Therefore, mercy killing and euthanasia which have become controversial issues in the medical profession are issues that have no support in any sect of Islam, while the perspectives of other religions regarding these issues are different